La guerre en Syrie dans la presse en ligne - Lazar, Jan (Linguistica (Ljubljana), 2018)
A war is defined as a conflict between two or more countries, states, social groups, individuals, with or without an armed struggle. Currently the Western me-dia, including online press, are very interested in the Syrian war. The Syrian civil war broke out in the context of the Arab Spring, starting with mostly peaceful dem-onstrations in favour of democracy and against the Baathist regime led by presi-dent Bashar al-Assad. It quickly turned into an armed rebellion that demanded the intervention of some Western countries, thus provoking much discussion. In this paper we try to understand how the phenomenon of war can intervene in the choice of identity disclosure of internet users. It should be pointed out that the choice of a username is one of the first acts undertaken by an internet user, and that before expressing oneself one has to identify oneself. The aim of this article is to analyse the relationship between the language use in comments and the digital identity of their producers. We also examine whether the possibility of hiding one's true identity is a trigger factor for the use of slang words. To answer these questions we propose a comparative study of two corpora of public commentaries appearing in online press sites that describe the war in Syria. The first corpus consists of Czech sites (Idnes.cz, Blesk.cz), whereas the second one is made up of French sites (20.minutes.fr, Closer.fr), according to an identical protocol.
Keywords: analiza diskurza; besedišče; češčina; francoščina; Sirija; spletna identiteta; spletne revije; spletni komentarji; vojna